Dynamic factor demands in a changing economy: an Irish application - McQuinn, Kieran (Economic & Social Studies, 2005)
In this paper a model of dynamic factor demands is presented for the Irish economy. Total costs, labour and capital are modelled on a two-stage basis. First, a static, long-run cost function is specified which allows for the derivation of expressions for optimal labour and capital demand. This function is assumed to be of the flexible, translog form and thus more general than the generic Cobb-Douglas application. In the second stage, a dynamic cost function is specified which nests the long-run static approach. Growth rates in factor shares are derived from the dynamic approach and the rate of adjustment of input use to factor price changes is examined through the use of short and long-run elasticities.
Keywords: Dynamic factors; Irish economy; Supply side economics; Economic growth